MULTIPLE ANTIBACTERIAL AND PHYTOCHEMICAL ANALYSIS OF MANGO KERNEL EXTRACTS ON AQUATIC AND ANIMAL PATHOGENS - SWAGATIKA SAHU,; BASANTA KUMAR DAS,; BIBHUDENDU KUMAR MISHRA, (International Journal of Pharma and Bio Sciences, 2013)
The antibacterial activities of hexane, ethyl acetate, acetone, ethanolic, methanolic and aqueous extracts of Mangifera indica kernel were studied in vitro against aquatic pathogens viz. Aeromonas hydrophila (six strains), Pseudomonas putida (three strains), P. aeruginosa (three strains), P. fluorescens (two strains), Flavobacterium columnare (three strains), Vibrio parahaemolyticus (two strains), V. alginolyticus (two strains), V. fluvialis, V. harveyi, Edwardsiella tarda (two strains) and animal pathogen, Escherichia coli (five strains). The ethanolic extract showed higher antibacterial activities against almost all tested microorganisms with minimum inhibitory concentration (MIC) ranged from 200-300μg. The highest zone size were exhibited in acetone extract (22.16mm/400μg) against one strain of A. hydrophila and ethanolic extract (19mm/400μg) against three strains of A. hydrophila and one strain of P. aeruginosa. The MIC of aqueous extract was 250-400μg with zone size ranged of 7.66-13.5mm. In phytochemical analysis, ethanolic, methanolic and aqueous extract showed the presence of saponin, flavonoid, alkaloid, tannin and sterol. The study showed that various extracts of mango kernel have potentialities in using against aquatic bacterial pathogens.